Biogeography and tropical terrestrial ecosystem health - Baguinon, Nestor T. (Asia Life Sciences : the Asian International Journal of Life Sciences, 2008)
Ecosystem health was discussed within the context of biogeography. The recorded number of animal and plant species can be ideal as standard for species completeness, hence ecosystem health. However, the idea is not practical. Small mobile organisms are difficult to account, unlike trees. Trees are obvious to monitor ecosystem health. The decrease of tree species number as a function of shrinking area due to deforestation is consistent with MacArthur and Wilson's Island Biogeography Theory (IBT). Natural ecosystems are alienated into agroecosystems, a relationship described as P (the natural ecosystem)= 1-Q (agroecosystem). Q expands at the expense of P and this results in forest fragmentation, irreversible destruction of habitats and extinction of species. Their ratio, P/Q is a yardstick to ecosystem health, including interconnectivity of natural ecosystems at various spatial and temporal scales. The regions Greater Mindanao, Samar-Leyte and the Central Cordillera Highlands had their tree flora data-based. Attributes such as elevation preferences and habitat were selected. Habitats ranged from primary forest to open grassland areas and seashores. Elevation ranged from seashore to several zones beyond sea level. Recorded tree species show that for all regions, primary forest dwelling species are at risk to extirpation or extinction. Philippine forest cover sharply declined from 1990 to 1999. Forest decline was overlaid with a topographic and a mining risk assessment map. Results show climax tree species are at high risk to extinction in Mindanao, Samar-Leyte and Cordillera. Remote sensing with ground truth inventory of tree species are activities that should measure ecosystem health. The discrepancy between actual and recorded tree species should measure ecosystem health deterioration. Presence of logging, swidden farming and mining are stress factors that enhance extinction of tree species and should include as criteria to poor ecosystem health. Said ecosystem stressors can be further exacerbated by anthropogenic climate change. Bioinvasion is another emerging threat. Social criteria are as important but have only been here enumerated.